2015
DOI: 10.1086/679758
|View full text |Cite
|
Sign up to set email alerts
|

Cuticular Patterns on Stylar Hairs in Asteraceae: a New Micromorphological Feature

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The University of Chicago Press is collaborating with JSTOR to digitize, preserve and extend access to International Journal of Plant Sciences.Editor: Patrick S. Herendeen Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
2
5
0
1
Order By: Relevance
“…A longitudinal cuticular pattern was detected on the stylar and filament hairs in the C. cyanus flowers. Our observations are in agreement with the data on the cuticular pattern on stylar hairs reported by Erbar and Leins (2015) for the Cardueae tribe. The longitudinal pattern on stylar hairs is observed in Asteraceae relatively frequently; for instance, Erbar and Leins (2015) have described this trait in 17 of all the 44 tribes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A longitudinal cuticular pattern was detected on the stylar and filament hairs in the C. cyanus flowers. Our observations are in agreement with the data on the cuticular pattern on stylar hairs reported by Erbar and Leins (2015) for the Cardueae tribe. The longitudinal pattern on stylar hairs is observed in Asteraceae relatively frequently; for instance, Erbar and Leins (2015) have described this trait in 17 of all the 44 tribes.…”
Section: Discussionsupporting
confidence: 93%
“…A new micromorphological feature, i.e. cuticular patterns on stylar hairs, was observed in members of all tribes (44) of the Asteraceae family (Erbar and Leins 2015). The authors of those studies reported five types of cuticular striation: crested, triple, double, longitudinal and transverse patterns.…”
Section: Introductionmentioning
confidence: 99%
“…The style appendages are papillose on both sides with densely, longitudinally striate cells (Fig. 3D), similar to those commonly found in other genera of Eupatorieae (Erbar & Leins, 2015).…”
Section: Leaf Natomysupporting
confidence: 81%
“…Stuessy et al (1996) suggested that apical appendages would be an adaptation to protect the pollen from humidity and insect predators, until the stigma and style push it up for pollen presentation. Recently, Erbar and Leins (2015) proposed the same function for the cuticular striation observed on the stylar hairs. Therefore, anther structures and the cuticular striation of the stylar hairs would seem to be related to the increase in the repellence of water drops in the florets.…”
Section: Micromorphological Charactersmentioning
confidence: 79%